Frontier and Developing Asia : The Next Generation of Emerging Markets - Schipke, Alfred (International Monetary Fund, 2015)
With a combined population of more than 350 million people, frontier and developing Asia, which includes countries such as Vietnam, Cambodia, and Bangladesh, is located in the world's fastest-growing region and has favorable demographics. The countries share a number of common macroeconomic, financial, and structural challenges. This book addresses issues related to economic growth and structural transformation, as well as the risk of a poverty trap and rising income inequality.